The space and the time in XXIII of Ameer almaneh - Amouri, Naim; Mokadem, Abdessaid (Journal of Human Sciences, 2023)
We studied time-place in the "twenty-third" stories; The importance of the place lies in the fact that it is a circumstance for the events, And in his employment of different places,drawing a picture of the deprivation suffered by the inhabitants of these places in their different times.Our studied concluded that most of the places used by the writer express poverty and deprivation; Some of them started small and static, then grew and moved, and an encrypted place keep pace with the contemporary story, In most stories, the element of place prevailed over the element of time.